Description of Depik Fish (Rasbora Tawarensis) Lipid Content in Laut Tawar Lake Aceh Tengah - Syahrin Novia; muhammad isa; Razali Razali (Universitas Syiah Kuala, 2014)
This study was aims to determine the fat content of depik fish (Rasbora tawarensis) collected from Laut Tawar Lake Central Aceh. The samples used were fresh fish from traditional catching around Laut Tawar lake with the weight of 12.45 and 12.74 gram. The samples were analyzed by Soxhlet method with two repetitions. The result of this study showed that the fat content of depik fish was 6,50%. It can be concluded that depik fish from Laut Tawar lake Central Aceh had average of fat content of 6,50%.Key words: Rasbora tawarensis, Laut Tawar, Aceh Tengah